Identification by families of pediatric adverse events and near misses overlooked by health care providers - Daniels, Jeremy P. (Canadian Medical Association, 2012)
BACKGROUND: Identifying adverse events and near misses is essential to improving safety in the health care system. Patients are capable of reliably identifying and reporting adverse events. The effect of a patient safety reporting system used by families of pediatric inpatients on reporting of adverse events by health care providers has not previously been investigated. METHODS: Between Nov. 1, 2008, and Nov. 30, 2009, families of children discharged from a single ward of British Columbia’s Children’s Hospital were asked to respond to a questionnaire about adverse events and near misses during the hospital stay. Rates of reporting by health care providers for this period were compared with rates for the previous year. Family reports for specific incidents were matched with reports by health care providers to determine overlap. RESULTS: A total of 544 familes responded to the questionnaire. The estimated absolute increase in reports by health care providers per 100 admissions was 0.5% (95% confidence interval −1.8% to 2.7%). A total of 321 events were identified in 201 of the 544 family reports. Of these, 153 (48%) were determined to represent legitimate patient safety concerns. Only 8 (2.5%) of the adverse events reported by families were also reported by health care providers. INTERPRETATION: The introduction of a family-based system for reporting adverse events involving pediatric inpatients, administered at the time of discharge, did not change rates of reporting of adverse events and near misses by health care providers. Most reports submitted by families were not duplicated in the reporting system for health care providers, which suggests that families and staff members view safety-related events differently. However, almost half of the family reports represented legitimate patient safety concerns. Families appeared capable of providing valuable information for improving the safety of pediatric inpatients.